Schooling and Inclusive Education During the Pandemic in Amazonas (Research, Society and Development, 2022)
This article aims to evaluate the impacts of the COVID-19 pandemic on inclusive education in Amazonas. The methodology used was the narrative documentary study involving scientific articles, journalistic materials, specialized education magazines, official reports and books on the subject produced during the pandemic period (from 2019 to 2022) or about ensuring inclusive education in the pandemic scenario that affected the whole world, due to COVID-19. Therefore, the criteria adopted for bibliographic selection were mainly those of theoretical foundation, methodological clarity and originality. In addition, we problematize the teaching laws in their extension and reach for all, as well as the inventive capacity and resilience of education professionals, especially in the state of Amazonas, in search of improvements and alternatives to maintain quality education even if in the remote modality, despite the social difficulties experienced by the Brazilian people, which became increasingly evident. Finally, we understand that the difficulties evidenced throughout 2020 and also 2021, it was possible to say that education projects, during the pandemic, proved to be flawed and left as a mark, a delay in the teaching- learning development process in all spheres of education in the state of Amazonas.